(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3eY gPG GdTjA GdeJhge Cfg GdTQW GdhGbYj aj MGd bjGe (B... (3bhdg aj chfg hGajG HJeGe GdZQV, hPdc EPG cGf GdTjA GdPj bGeI GdEeGQI Ydjgs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg Hd ef GdebOeGJ GdZjQ GdGNJjGQjI adG jJYdb GdWdH JQcgG, bhdg hEdG dJSdSd Cj hEf de Jcf GNJjGQjI dJSdSdJ eHGOF GdGNJjGQ aJCeds
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs